101 Telco Solutions offers fuel cell backup power from Altergy. Issue 10 (October 2018) - Unknown
Abstract : California-based Altergy Systems has formalised its partnership with 101 Telco Solutions, a leading provider of high-end electronic equipment repair, distribution, and technical services. Altergy's PEM fuel cell backup power systems offer a more reliable, economical and 'green' solution to conventional generators and inefficient 'short-life' battery systems.